MENUMBUHKEMBANGKAN KARAKTER CINTA LINGKUNGAN PADA ANAK SEKOLAH DASAR BERBASIS PERTANIAN ORGANIK - Rahayuningsih, Sri; Rahaju, Juli; Rahayu, Yekti Sri (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2017)
Nowadays, The Environmental damage has become a very important issue, because the impact has been felt by peoples in the world. Causes of the Environmental damage is consists to natural factors and human factors. The purpose of this program has cultivated love attitude to environment early, in order to students who has knowledge and love of the environment. Method of implementation includes counseling, training, teaching, demonstration and practice so that learning more interesting and be absorbed by the student. The results of the implementation of this service activities such as knowledge of teachers and students in a matter of love environment.The enthusiasm of students in participating in this activity is very high. This is evident from the number of participants who take part in a very satisfactory rate of more than 80%. Demo sorting garbage and organic vegetable cultivation practices in schools also done well and the results are satisfactory although students still have to obtain further guidance and assistance.